Analysis of Factors Forming Work-Life Balance in Hotel Employees in the Special Regional Province of Yogyakarta - Ambar Kusuma Astuti; Alfa Santoso Budiwidjojo Putra; Purnawan Hardiyanto (International Journal of Management Science and Application, 2024)
Hospitality has a strategic role in supporting the smooth running of the tourism industry. However, high job demands often cause employees to experience fatigue. So that all activities carried out run harmoniously, employees need to experience work-life balance. This study uses role theory to observe the phenomena of an employee's work and non-work life. The location for primary data collection was the Special Region of Yogyakarta Province, Indonesia. The research respondents were married hotel employees. The questionnaire uses a Likert scale with five choices. The research instrument was adapted from previous studies. The number of questionnaires that can be processed is ninety-six. The data analysis technique uses exploratory factor analysis. Before factor analysis was carried out, the primary data collected was filtered first using KMO and Bartlett's Test of Sphericity. Varimax is used to determine new factors. From the test, six factors shape work-life balance. The names of the new factors include a meaningful career, family obligations, diligent work, a comfortable home, fun at work, and how to be successful. Meanwhile, the most dominant factor is a meaningful career.